Reconceptualizing Al-Sāriq: Linguistic And Maqâshid-Based Analysis Of Electronic Embezzlement And Digital Manipulation - Muhammad Rusdi bin Muhammaddiah; Awwaluz Zikri; Izdihar Nurul Fajar; Umami, Yusra (Al-'Adl, 2026)
Digital transformation has reshaped the landscape of corruption and challenges classical Islamic criminal law. This article reconceptualizes al-Sāriq for digital corruption through a qualitative textual study that integrates classical Islamic legal hermeneutics with contemporary linguistics. the study aims to trace the evolution of the meaning of al-Sāriq, construct an adaptive framework for cyber-enabled offenses, and formulate implementation strategies within modern justice systems. Using text analysis, it combines comprehensive linguistic inquiry on al-Sāriq, the integration of maqâshid al-sharia with technological developments, and strategy development through case studies and comparative legal reviews. Findings indicate that al-Sāriq extends beyond physical theft to encompass unauthorized appropriation and manipulation of digital assets. The maqâshid-oriented framework broadens legal protection to digital assets, institutional reputation, and social stability, enabling proportionate calibration between ḥudūd and ta‘zīr in complex schemes. The proposed conceptual model allows Islamic criminal law to respond effectively to digital corruption without compromising sharia principles. The study underscores the necessity of an interdisciplinary approach and the adaptive capacity of Islamic law, while offering sanction models that are proportional, restorative, and responsive to contemporary corruption dynamics.